2009
DOI: 10.1080/14613800903390741
|View full text |Cite
|
Sign up to set email alerts
|

The struggle between globalisation, nationalism and music education in Hong Kong

Abstract: The year 2008 marked the 11th anniversary of Hong Kong's return from the UK to the People's Republic of China. In this decade, the Hong Kong Special Administrative Region Government has repeatedly emphasised the importance of the development of national identity and patriotism in school education, and has at the same time introduced diverse cultural values into the school curriculum. This article explores the dynamics and complexity of the relationships between the state, globalisation and nationalism in Hong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…The topics of patriotism, nationalism, and national identity in music education have been the subject of recent scholarly inquiry (Abril, 2007; Bartel, Dollof, & Shand, 1999; Beegle, 2004; Bodnar & Gilboa, 2009; Brand, 2003; Hebert, 2006; Ho & Law, 2003, 2009; Hollington, 2005; Jorgensen, 2007; Veblen, in press). Issues addressed are the connections between patriotism, nationalism, and globalization in music education (Hebert, 2006; Ho & Law, 2003, 2009), the role played by the content of music education curricula in cultivating patriotism and/or a sense of national identity (Bartel et al, 1999; Brand, 2003; Ho & Law, 2003; Hollington, 2005), the connection between the national anthem and national identity (Bodnar & Gilboa, 2009; Veblen, in press), and critique of the use of the national anthem in schools in one jurisdiction (Abril, 2007; Beegle, 2004; Jorgensen, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topics of patriotism, nationalism, and national identity in music education have been the subject of recent scholarly inquiry (Abril, 2007; Bartel, Dollof, & Shand, 1999; Beegle, 2004; Bodnar & Gilboa, 2009; Brand, 2003; Hebert, 2006; Ho & Law, 2003, 2009; Hollington, 2005; Jorgensen, 2007; Veblen, in press). Issues addressed are the connections between patriotism, nationalism, and globalization in music education (Hebert, 2006; Ho & Law, 2003, 2009), the role played by the content of music education curricula in cultivating patriotism and/or a sense of national identity (Bartel et al, 1999; Brand, 2003; Ho & Law, 2003; Hollington, 2005), the connection between the national anthem and national identity (Bodnar & Gilboa, 2009; Veblen, in press), and critique of the use of the national anthem in schools in one jurisdiction (Abril, 2007; Beegle, 2004; Jorgensen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hebert (2006) and Ho and Law (2003, 2009) investigated issues of patriotism and music education in Asia-Pacific countries. Ho and Law (2003, 2009) examined music education in contemporary Taiwan and Hong Kong, discussing the impact of globalization and nationalism on countries where Confucian moral values are strong, in the case of Taiwan, and where Western values were formerly dominant, in the case of Hong Kong. The authors concluded that the interplay between former ideologies and 21 st -century government and global influences present a unique challenge for music educators in these two countries.…”
Section: Introductionmentioning
confidence: 99%
“…Garlake ( 2007) points out that the acceleration of globalization and the spread of global brands (see Interbrand, 2010) over the last quarter-century has resulted in greater cultural homogeneity around the world, as these global brands also export culture (see Ritzer, 2008). Tomlinson (1999, in Ho andLaw, 2009) corroborates this view, asserting that the influence of 'global culture', or globalism, has led to the 'cultural disorientation' of young people around the world. Jandt (2010), conversely, argues that globalization has led to the strengthening of ethnic identity which, in extreme cases, has resulted in an increase in ethnic clashes (Chua, 2002, in Jandt, 2010.…”
Section: Globalism and Tribalismmentioning
confidence: 97%
“…Educational systems worldwide are being shaped by a dynamic 'global superstructure' (Loomis et al, 2008;Spring, 2009), policies from which filter into school systems -sometimes, but not always, being adapted to suit national and local cultures (Dale, 1999, in Ho andLaw, 2009). Global knowledge industries are gradually homogenizing the global education culture (see Spring, 2009), and curricula around the world are becoming increasingly similar (Meyer et al, 1992, in Hashimoto, 2003see International Review of Curriculum andAssessment Frameworks Internet Archive, 2009a, 2009b).…”
Section: Globalism and Tribalismmentioning
confidence: 99%
“…For countries with diversity, the integration of multicultural values in learning has proven to strengthen national identity [20]. The Hong Kong Special Administrative Region (SAR) government introduces diverse cultural values into the school curriculum to maintain national identity through education [21]. In Indonesia, the implementation of multicultural values such as upholding justice, democracy, humanity, and pluralism has been done through strengthening education character regulation [22] in addition to the deconstruction idea of radicalization and racial conflict phenomenon through empowering moderate Islamic value [23].…”
Section: Introductionmentioning
confidence: 99%